Density, Distribution and Staining Properties of Eosinophilic Granular Cells in Oscar Fish (Astronotus ocellatus) Intestine - Öztop, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Fish eosinophilic granular cells are found in the connective tissues of structures associated with the external environment. These cells are similar to mammalian mast cells in terms of structural and functional characteristics. The cytoplasmic granules of these cells give different staining reactions depending on fixative type. This study aimed to determine the staining properties and densities of eosinophilic granular cells in Oscar fish (Astronotus ocellatus Agassiz, 1831) intestine using different fixatives and histochemical techniques. Formalin and basic lead acetate fixation-giemsa staining indicated that eosinophilic granular cells were abundant in anterior intestine, localizing around especially the blood vessels and submucosa. Giemsa staining of Bouin’s fixed rather than other fixatives showed that eosinophilic granular cells were higher in posterior intestine. No reaction was observed in eosinophilic granular cells in Thionin and Toluidine Blue staining in any fixative. Eosinophilic granular cells in samples fixed with different fixatives had metachromatic Alcian Blue staining. In conclusion, this study shows that fixatives may have different effects on the distribution and staining properties of eosinophilic granular cells in Oscar fish intestinal regions. Abundance in anterior intestine and around submucosal blood vessels shows that eosinophilic granular cells could play an active role in mucosal immunity against food-borne pathogens.